Archaeology in Asia Minor - Mellink, M. J.
Palaeolithic Sites: Mağracık, Beldibi, Pendik, Şile — Chalcolithic and Bronze Age Sites: Kültepe, Horoztepe, Boğazköy, Karahüyük, Hacılar, Izmir-Bornova, Mysia, Kütahya, Bithynia, Dorak-Troy, Edirne — Iron Age and Classical Sites: Ankara, Gordion, Hergan Kale, Altıntepe, Toprakkale, Harran, Karatepe, Misis, Yesemek, Islahiye District, Tilmen Hüyük, Xanthos, Marmaris, Miletus, Panionion, Sardis . . .